PERANCANGAN MAKET TAMAN HIBURAN PANTAI KENJERAN SEBAGAI MEDIA INFORMASI DAN PROMOSI WISATA SURABAYA - Arum Sya’bana; Rizka Rahma Amalia (Universitas Trisakti, 2025)
3D Design Model of Kenjeran Beach Amusement Park as Information and Promotion Media for Surabaya Tourism. Kenjeran Beach Amusement Park (THP) is a tourist destination with significant potential as a tourism icon in Surabaya. However, the area currently lacks visual information media that can provide a comprehensive overview of the layout and available facilities, such as a tourist map. This study aims to design a 3D mockup to serve as a tourism information and promotion tool for Kenjeran Beach Amusement Park. The mockup design used a freehand sketching method and an environmentally friendly approach through the use of recycled materials. Data was collected through observation, interviews, and literature review. The mockup was designed at a scale of 1:1000, showcasing all the buildings and facilities of Kenjeran Beach Amusement Park in three-dimensional form. The resulting mockup of Kenjeran Beach Amusement Park will serve as a tourism map. It is hoped that it will facilitate visitor access to information on the site and serve as an effective promotional tool to attract investors. The results of this study can also serve as a reference for Kenjeran Beach Amusement Park management in developing future promotional strategies.